2020
DOI: 10.1088/1755-1315/614/1/012126
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of Mung bean (Vigna radiata(L.)) depending on sowing methods

Abstract: The article presents the value of the legume crop - mung bean, as a high-protein, nitrogen-fixing, and also gives the results of research work on the study of the influence of the seeding scheme and rate on the growth, development and yield of mung bean (Vigna radiata(L.)). Research results have shown that sowing methods affect the length of the developmental phases, the formation of leaf area, the net productivity of photosynthesis and the yield of mung bean. As a result of an increase or decrease in the seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…3). It should be noted that, compared, for example, with the studies of N. A. Ravshanova [45], under the condition of introduction in the Right-Bank Fo- The study of morphological indicators depending on the phase of development allows not only to establish the general and distinctive features of plants, but to assess the productive potential of the introduced species. It was found that representatives of the genus Vigna are characterized by significant variability of biometric characteristics (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3). It should be noted that, compared, for example, with the studies of N. A. Ravshanova [45], under the condition of introduction in the Right-Bank Fo- The study of morphological indicators depending on the phase of development allows not only to establish the general and distinctive features of plants, but to assess the productive potential of the introduced species. It was found that representatives of the genus Vigna are characterized by significant variability of biometric characteristics (Fig.…”
Section: Resultsmentioning
confidence: 99%